Derived Words from Pali and Sanskrit Words Written in Ramayana Drama a Writing by His Majesty King Phra Buddha Lertla Naphalai - Tongrakjan, Pattiya; Chaipunya, Chittapa Sarapadnuke (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This qualitative study aims to introduce the study of the sources, synonym words of derived words from Pali and Sanskrit words written in Ramayana drama, a writing by His Majesty King Phra Buddha Lertla Naphalai. The findings indicated that there are 750 words of derived Pali and Sanskrit words can be classified into 4 aspects, including 210 words of derived from Pali words, 281 words of derived from Sanskrit words, 229 words of derived between Pali and Sanskrit words and 30 words from Pali and Sanskrit words that were created and used in Thai language. There are 14 meaning of synonyms, including gods and devils, body organs, places, natures, objects, properties, characteristics, verbs, emotions, time, numbers, works and etc. All of them has a subdivision meaning into 163 meanings